The Effect of the Numbered Head Together Cooperative Learning Model Assisted by the Quizlet Application on Students’ Mathematical Concept Understanding Ability - Adawiyah Ritonga; Fibri Rakhmawati (Universitas Sembilanbelas November Kolaka, 2026)
This study aimed to determine the effect of the Numbered Head Together (NHT) cooperative learning model assisted by the Quizlet application on students' mathematical conceptual understanding ability in the topic of relations and functions. The study employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The sample consisted of 30 students from class VIII-B. The research instrument was a mathematical conceptual understanding test administered before and after the treatment. Data were analyzed using the Shapiro-Wilk normality test, Levene homogeneity test, Paired Sample t-Test, Cohen’s d effect size analysis, and N-Gain test. The results showed that the average pretest score of 54.47 increased to 80.00 in the posttest. The hypothesis test yielded a significance value of 0.000 0.05, indicating a significant effect of the NHT learning model assisted by Quizlet on students' mathematical conceptual understanding ability. The effect size analysis produced a Cohen’s d value of 5.03, which falls into the large category. Meanwhile, the N-Gain value was 0.563 or 56.33%, categorized as moderate, indicating that the learning process was sufficiently effective in improving students' mathematical conceptual understanding. Therefore, the NHT cooperative learning model assisted by the Quizlet application can be considered an effective alternative for enhancing students' mathematical conceptual understanding